Integrating Virtual Reality in STEM Education: Enhancing Engagement and Learning Outcomes - Dara Sovann; Sopheap Chan; Makara Lay (International Journal of Educational Technology and Society, 2024)
This study investigates the impact of virtual reality (VR) tools in enhancing student engagement and learning outcomes in STEM (Science, Technology, Engineering, and Mathematics) education. By analyzing experimental data from VR-based STEM lessons across multiple schools, the research highlights how immersive experiences can help students understand complex concepts, increase motivation, and improve retention. The findings emphasize the potential of VR to transform traditional STEM education by providing interactive and engaging learning environments.